Enabling Sustainable Livestock Development: ‘CLEANED’ tool effectively supports Environmental Impact Assessments across 34 countries across Africa, Asia, and Latin America. - Notenbaert, An; Mwema, Emmanuel; Gonzalez, Ricardo; Van Der Hoek, Ringenerus; Isiaho, Glarion; Ewell, Hanna (2025)
By generating evidence of environmental footprints, our impact-assessment tool ‘CLEANED’ improves sustainable livestock enterprise planning. Numerous trainings/workshops have taught the next users (researchers, livestock-industry stakeholders, educators, and policy advisors) how to use CLEANED effectively. Several CLEANED assessments have been conducted (of which 20 have been documented), presented to, and discussed with decision-makers at different levels throughout Africa, Asia, and Latin America. This has led to greater environmental awareness and environmentally-sensitive planning of livestock interventions.